Association between plasma endothelial microparticles and contrast-induced nephropathy in patients underwent coronary angiography. Issue 28 (16th July 2021) - Fu, Xiaodan; Dong, Jing; Wang, Hongyan; Lou, Dayuan; Li, Xin; Mei, Jiajie; Sui, Zheng; Yang, Qian; Niu, Nan; Qu, Peng
Abstract : Abstract: We aim to investigate the association between plasma endothelial microparticles (EMPs) and contrast-induced nephropathy of patients underwent coronary angiography. The patients were divided into normal renal function group and renal dysfunction group based on the estimated glomerular filtration rate (eGFR). Among the 180 cases, 117 received determination of EMP and serum creatinine after percutaneous coronary intervention (PCI) and/or coronary angiography. The patients were divided into contrast-induced-nephropathy (CIN) group and non-CIN group. EMPs collection and determination were performed, together with biochemical analysis and digital subtraction angiography (DSA) analysis. Spearman correlation showed that the expression of EMP was negatively correlated with eGFR ( r = –0.201, P < .01). The serum hypersensitive C-reactive protein (hs-CRP), cystatin C (Cys-C), uric acid (UA) were significantly higher in CIN group than that in the non CIN group. Spearman correlation showed that the expression of EMP was positively correlated with serum interleukin-6 (IL-6, r = 0.393, P < .01). The expression of EMP was positively correlated with serum hs-CRP ( r = 0.360, P < .01). Logistic regression analysis showed that the levels of N-terminal pro-brain natriuretic peptide (NT-proBNP), eGFR, UA, and Cys-C were correlated with the incidence of contrast induced nephropathy. In patients with contrast-induced-nephropathy, the plasma EMPs were significantly increased after coronary angiography. The expression of plasma EMPs may play a role in the occurrence of contrast-induced-nephropathy.